Anaerobic ammonium oxidation driven by dissimilatory iron reduction in autotrophic Anammox consortia. (November 2022) - Wang, Zhenxin; Sun, Cheng; Zhou, Yue; Yu, Qilin; Xu, Xiaochen; Zhao, Zhiqiang; Zhang, Yaobin
Graphical abstract: Highlights: The nitrogen removal rate of Anammox sludge increased by 39 % with adding Fe(OH)3 . Feammox generated 30 N2 was observed in an Anammox consortia. Fe(OH)3 spurred the EET related enzyme activity of Anammox sludge. Electron-storage capacity of Anammox sludge increased with Fe(OH)3 . Abstract: Feammox has been applied to wastewater biological nitrogen removal. However, few studies have reported that Fe(III)(hydr)oxides induced Anammox consortia to remove NH4 + via the Feammox pathway. In this study, Fe(OH)3 was added to Anammox systems to investigate its effect on nitrogen removal via Feammox. The specific Anammox activity increased by 39 % by Fe(OH)3 . Ammonia oxidation was observed to occur along with Fe(III) reduction and Fe(II) generation, which was further confirmed by the isotope test with feeding 15 NH4 + -N to detect 30 N2 . The cyclic voltammetry test showed that electron-storage capacity of Anammox sludge increased with Fe(OH)3 . In situ Fourier transform infrared spectroscopy suggested that Fe(OH)3 enhanced the polarization of functional groups of outer membrane cytochrome of Anammox consortia to benefit extracellular electron transfer. This study demonstrated that Fe(OH)3 could induce Anammox consortia to perform extracellular respiration to enhance NH4 + -N removal in the Anammox sludge system.